Paracellular and transcellular migration of metastatic cells through the cerebral endothelium. Issue 4 (2nd February 2019) - Herman, Hildegard; Fazakas, Csilla; Haskó, János; Molnár, Kinga; Mészáros, Ádám; Nyúl‐Tóth, Ádám; Szabó, Gábor; Erdélyi, Ferenc; Ardelean, Aurel; Hermenean, Anca; Krizbai, István A.; Wilhelm, Imola
Abstract: Breast cancer and melanoma are among the most frequent cancer types leading to brain metastases. Despite the unquestionable clinical significance, important aspects of the development of secondary tumours of the central nervous system are largely uncharacterized, including extravasation of metastatic cells through the blood‐brain barrier. By using transmission electron microscopy, here we followed interactions of cancer cells and brain endothelial cells during the adhesion, intercalation/incorporation and transendothelial migration steps. We observed that brain endothelial cells were actively involved in the initial phases of the extravasation by extending filopodia‐like membrane protrusions towards the tumour cells. Melanoma cells tended to intercalate between endothelial cells and to transmigrate by utilizing the paracellular route. On the other hand, breast cancer cells were frequently incorporated into the endothelium and were able to migrate through the transcellular way from the apical to the basolateral side of brain endothelial cells. When co‐culturing melanoma cells with cerebral endothelial cells, we observed N‐cadherin enrichment at melanoma‐melanoma and melanoma‐endothelial cell borders. However, for breast cancer cells N‐cadherin proved to be dispensable for the transendothelial migration both in vitro and in vivo. Our results indicate that breast cancer cells are more effective in the transcellular type of migration than melanoma cells.